Volume 4: Materials Technology; Ocean Engineering 2007
DOI: 10.1115/omae2007-29178
|View full text |Cite
|
Sign up to set email alerts
|

Calculation Methodology of Out of Plane Bending of Mooring Chains

Abstract: Recently, the phenomenon of out-of-plane bending (OPB) fatigue of mooring chain links emerged as an important parameter in the fatigue assessment of mooring lines. Vessel motions induce a bending moment at the top chain of a mooring line. This bending moment induces alternating local stresses in the link and thus contributes to fatigue damage of those links. High pretension mooring systems are particularly sensitive to this phenomenon, since a small vessel motion combined with a high tension results in a relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Vargas et al provided procedures for calculating the stress concentration factors (SCF) of chain links subjected to OPB loads using finite-element analysis (FEA) [6]. Subsequently, many studies investigated the OPB fatigue phenomenon of mooring chains using either FEA or experimental methods [3,4,[7][8][9][10][11], and the phenomenon and failure mechanism of OPB were studied and interpreted, as shown in Figure 2 [12]. The relationship between OPB stresses in mooring chains and pretension, interlink angles, and mooring chain materials has been established in related studies [3]; moreover, it was also found that high OPB stresses will be induced in the proof loading test [8].…”
Section: Introductionmentioning
confidence: 99%
“…Vargas et al provided procedures for calculating the stress concentration factors (SCF) of chain links subjected to OPB loads using finite-element analysis (FEA) [6]. Subsequently, many studies investigated the OPB fatigue phenomenon of mooring chains using either FEA or experimental methods [3,4,[7][8][9][10][11], and the phenomenon and failure mechanism of OPB were studied and interpreted, as shown in Figure 2 [12]. The relationship between OPB stresses in mooring chains and pretension, interlink angles, and mooring chain materials has been established in related studies [3]; moreover, it was also found that high OPB stresses will be induced in the proof loading test [8].…”
Section: Introductionmentioning
confidence: 99%
“…The rupture occurred eight months after the installation and was not predicted by industry standards. Therefore, this loading mode attracted the attention of several research programs and multiple publications can be found in the literature, see for example [7,9,[22][23][24][25][26][27]. Among this effort in understanding and quantifying Out-of-Plane Bending, it is worth mentioning a Joint Industry Program (JIP) gathering 28 different companies whose objectives were a better understanding of Out-of-Plane Bending fatigue and propose fatigue design recommendations, their main findings can be found in [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Ter Brake et al [5] presented an S-N curve based fatigue analysis for mooring chains, in which the effects of the OPB on mooring chain stresses were determined by a FE analysis of chain links. Melis et al [6] presented experimental results of mooring chain stresses induced by OPB.…”
Section: Introductionmentioning
confidence: 99%